Experiences of Community Health Workers (CHWs) and their wellbeing: A study of CHWs in Johannesburg Townships - Mashinini, Lethiwe Yvonne (University of the Witwatersrand, Johannesburg, 2023)
Community Health Workers (CHWs) have become important role players in the provision of health and social services in many underprivileged communities around South Africa. Despite the role and impact of these cadres in many communities, few studies have focused on the impact of their work on their wellbeing. Hence, the study's interest in expanding its inquiry on the experiences of CHWs and their impact on the cadre's wellbeing. This research further inquired about the national CHWs policy and CHWs scope of practice facilitated through the WBPHCOTs strategy that resulted from the re-engineering of the PHC model. As an observer qualitative data was collected through non-participative observation. Drawing from in-depth interviews this study further examined and describes the self-reported experiences of CHWs and NGO managers. To frame the experiences of CHWs and the impact of these experiences on their wellbeing the research findings were theorized from the perspective of social constructionism. The fundamental concern was to understand how cadres define, describe, and think about different social aspects of their life as CHWs and how these experiences influence their reality. Specifically focusing on two NGOs situated in Johannesburg townships the study participants were composed of eight CHWs (six female and two male cadres) as well as two male managers who were consulted as key informants. Concerning the national CHWs policy and the guiding scope of practice in the functioning of CHWs, the research yielded interesting findings. The managers of the NGOs were unaware of the existence of the national policy framework dubbed the Ward-based primary healthcare outreach team’s strategy (WBPHCOTs) policy framework. Hence, the organizations had not adopted or aligned the work of CHWs with the WBPHCOTs strategy policy framework. Instead, the NGOs maintained their arrangement of CHWs programmes as multi-stakeholder projects. This raises concerns about the implementation of the WBPHCOTs policy framework as a national CHWs policy, particularly in the NGO sector. The research also revealed multifaceted findings about CHW's experiences, which were largely positive and influenced by altruistic sentiments. Cadres also felt a sense of self-development and the possibility of improvement in their lives, which had a positive impact on their social wellbeing. CHWs also encountered some negative experiences such as challenging working conditions and poor remuneration and this had adverse impacts on their physical, psychological, and economic wellbeing. Therefore experiences of CHWs impacted their wellbeing both positively and negatively.
A research project submitted in partial fulfillment of the requirements for the Degree of Masters of Art (coursework and research) in Health Sociology, School of Social Sciences, with the Faculty of Humanities, University of Witwatersrand, Johannesburg, 2022.
Keywords: Community Health Workers (CHWs); Cadres; Experiences; NDOH; NGOs; PHC system; Wellbeing; UCTD; SDG-3: Good health and well-being